2012
DOI: 10.1103/physrevd.86.115004
|View full text |Cite
|
Sign up to set email alerts
|

Holographic technidilaton at 125 GeV

Abstract: We find that a holographic walking technicolor model has a limit ("conformal limit") where the techni-dilaton (TD) becomes a massless Nambu-Goldstone boson of the scale symmetry with its nonzero finite decay constant F φ = 0, which naturally realizes a light TD, say at 125 GeV, near the limit. In such a light TD case, we find that F φ is uniquely determined by the techni-pion decay constant Fπ independently of the holographic parameters: F φ /Fπ ≃ √ 2NTF, with NTF being the number of techni-fermions. We show t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

28
185
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(213 citation statements)
references
References 60 publications
28
185
0
Order By: Relevance
“…It was shown that the TD can account for the 125 GeV Higgs, with couplings that are consistent with the current LHC data of the 125 GeV Higgs (see below) [8][9][10][11]. Thus the origin of the Higgs mass is dynamically explained by the scale of the chiral condensate in WTC.…”
Section: Introductionsupporting
confidence: 48%
See 3 more Smart Citations
“…It was shown that the TD can account for the 125 GeV Higgs, with couplings that are consistent with the current LHC data of the 125 GeV Higgs (see below) [8][9][10][11]. Thus the origin of the Higgs mass is dynamically explained by the scale of the chiral condensate in WTC.…”
Section: Introductionsupporting
confidence: 48%
“…A precise ladder evaluation of m φ F φ based on this PCDC relation reads [12]: (m φ F φ ) 2 More recently, in another approach using holographic WTC [15] it was shown [11] that the strong gluon dynamics via the large technigluon condensate can realize a parametrically massless TD limit m φ /v EW → 0+ and hence naturally realize m φ ≃ v EW /2 ≃ 125 GeV, consistent with the LHC Higgs data. Similar arguments for realizing a parametrically light dilaton were given in somewhat different contexts [16].…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…• Pure singlet extension of the SM [55][56][57][58][59] • Hidden (dark) sector DM with hidden (dark) gauge symmetry [52][53][54][60][61][62][63][64][65][66][67] • Dilaton or radion [68][69][70][71][72][73][74][75][76][77][78][79][80] • Enhancing diphoton rate from vector-like(VL) fermions or new charged vector bosons [81][82][83][84][85][86][87][88][89] Determination of the Higgs couplings in the presence of a (light) singlet scalar boson has not been discussed properly in the recent literature (but, for some earlier attempts, see Refs. [16,27,40]).…”
Section: Introductionmentioning
confidence: 99%